2022
DOI: 10.3390/ma15217824
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Fabrication Method and Surface Modification of Alumina Ceramic on the Microstructure and Mechanical Properties of Ceramic–Elastomer Interpenetrating Phase Composites (IPCs)

Abstract: The paper presents experimental results of the work conducted to improve the adhesion between alumina ceramics and urea-urethane elastomer in the interpenetrating phase composites (IPCs), in which these two phases are interpenetrating three-dimensionally and topologically throughout the microstructure. Measurements of the contact angle, surface roughness, and shear tests were used to evaluate the effectivity and select the quantity of a silane coupling agent and the ceramic fabrication method. The tests were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Typically, methods for preparing IPC include pressureless infiltration, squeeze casting, and vacuum pressure infiltration, among others [ 13 ]. Squeeze casting and vacuum pressure infiltration processes are more complex, while the pressureless infiltration method for preparing IPC is relatively simple and enables low-cost industrial applications [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, methods for preparing IPC include pressureless infiltration, squeeze casting, and vacuum pressure infiltration, among others [ 13 ]. Squeeze casting and vacuum pressure infiltration processes are more complex, while the pressureless infiltration method for preparing IPC is relatively simple and enables low-cost industrial applications [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the polyurethane foam's high strain rate sensitivity, the energy dissipation of IPCs increased under dynamic compression by ~13.8% when compared to Al skeleton. 12 Moreover, Paulina Kozera et al 13 demonstrated the influence of fabrication techniques on the mechanical behaviour of alumina foams and elastomer in IPCs. The application of pressure in the fabrication process of elastomers into porous foams increased the mechanical strength from 25 to 33 MPa.…”
Section: Introductionmentioning
confidence: 99%
“…The application of pressure in the fabrication process of elastomers into porous foams increased the mechanical strength from 25 to 33 MPa. 13 Subsequently, Horny et al fabricated interpenetrating IPCs (aluminium/ alumina composites) using pressure infiltration, and the microstructural characteristics of the IPCs were examined in various aspects. 14 Also, open porous SiC foam/Zr-metallic glass IPCs were developed by Su et al using pressure infiltration.…”
Section: Introductionmentioning
confidence: 99%